(25^x)-(6(5^x))+5=0 for x
G Gragadoodle New member Joined Sep 5, 2013 Messages 16 Nov 16, 2013 #1 \(\displaystyle (25^x)-(6(5^x))+5=0\) for x
D Deleted member 4993 Guest Nov 16, 2013 #2 Gragadoodle said: \(\displaystyle (25^x)-(6(5^x))+5=0\) for x Click to expand... use 25 = 52 then substitute u = 5x Now you will have a quadratic equation, solve it using your favorite method and continue.....
Gragadoodle said: \(\displaystyle (25^x)-(6(5^x))+5=0\) for x Click to expand... use 25 = 52 then substitute u = 5x Now you will have a quadratic equation, solve it using your favorite method and continue.....